2021
DOI: 10.1007/s42452-020-04128-5
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and minimization of moment coefficient of tall buildings with trilateral cross-section via a surrogate model

Abstract: Wind load is commonly regarded as the dominant lateral load in designing tall buildings. Thus, it is of necessity to investigate the parameters affecting wind-induced loads. One of these parameters is the exterior shape of tall building, which using its aerodynamic shape modifications, wind loads, can be decreased. In this research, the exterior shape of different tall buildings with trilateral cross-section is constructed via the polynomial parameterization method. The advantage of the proposed method in prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…These functions were optimized in a bi-objective optimization process using NSGAII. The obtained results show the accuracy of the proposed method to increase the aerodynamic performance of tall 3D buildings [12]. A polynomial method is used for shape parameterization to construct the outer shape of buildings.…”
Section: Introductionmentioning
confidence: 70%
See 3 more Smart Citations
“…These functions were optimized in a bi-objective optimization process using NSGAII. The obtained results show the accuracy of the proposed method to increase the aerodynamic performance of tall 3D buildings [12]. A polynomial method is used for shape parameterization to construct the outer shape of buildings.…”
Section: Introductionmentioning
confidence: 70%
“…In this research, three optimized models of Noormahamadian and Salajaghe [20] named N1, N2, and N3 are used; the 4…”
Section: Model Description and Physicsmentioning
confidence: 99%
See 2 more Smart Citations
“…36 They highlighted the existing issues and their solutions and proposed some recommendations as well for future research. Instead of using CFD analysis, Noormohamadian and Salajegheh 37 used a function that explicitly model the moment coefficient of tall buildings with trilateral cross-sections as a surrogate model. In this paper, a comparison of the optimal model’s aerodynamic responses to the basic triangle model revealed that the moment coefficient was lowered by 56%.…”
Section: Introductionmentioning
confidence: 99%